Pengaruh Lokasi dan Daya Tarik Wisata terhadap Kepuasan Pengunjung Puncak Marga Silima - Handika Ramadhana; Wan Suryani; Muslim Wijaya (Jurnal Ilmiah Manajemen dan Bisnis (JIMBI), 2026)
This study aims to analyze the effect of location and tourist attraction on visitor satisfaction and to provide strategic recommendations for destination managers in improving the quality of the tourism experience at Puncak Marga Silima, Suka Makmur Village, Kutalimbaru District, Deli Serdang Regency. The research problem focuses on the decline in the number of visitors from 23,064 in 2023 to 14,519 in 2024, indicating the need to evaluate the aspects of location and tourist attraction in shaping visitor satisfaction. This study uses a quantitative approach with an associative research design. The population consisted of all visitors to Puncak Marga Silima in 2024, totaling 14,519 visitors. The sample consisted of 99 respondents selected using the Slovin formula with a 10% margin of error and purposive sampling technique. Data were collected through questionnaires and analyzed using SPSS with multiple linear regression, t-test, F-test, and coefficient of determination. This study concludes that location has a positive and significant effect on visitor satisfaction. Tourist attraction also has a positive and significant effect on visitor satisfaction. Simultaneously, location and tourist attraction have a positive and significant effect on visitor satisfaction. The Adjusted R Square value of 0.675 indicates that location and tourist attraction explain 67.5% of the variation in visitor satisfaction, while the remaining 32.5% is explained by other factors outside the research model. These findings indicate that visitor satisfaction can be improved by enhancing location accessibility, parking security, supporting facilities, environmental preservation, tourism attraction development, and the strengthening of local cultural potential.